2023
DOI: 10.1111/jan.15600
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' experience of managing adults living with multimorbidity: A qualitative study

Abstract: Background The number of adults living with two or more chronic conditions is increasing worldwide. Adults living with multimorbidity have complex physical, psychosocial and self‐management care needs. Aim This study aimed to describe Australian nurses' experience of care provision for adults living with multimorbidity, their perceived education needs and future opportunities for nurses in the management of multimorbidity. Design Qualitative exploratory. Methods Nurses providing care to adults living with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…14 Recent qualitative and mixed-methods studies of individuals with multimorbidity and complexity also reported that these patients expect nurses to be more cognizant of their living situations and social care needs and develop therapeutic interpersonal relationships to enhance the delivery of integrated and compassionate care. 2,15,16 Families of individuals with multimorbidity and complexity and health care teams are important partners in the delivery of person-centered integrated care. 17,18 Scoping reviews have highlighted that enhanced collaboration among health care professionals and families of patients is crucial for the delivery of integrated care.…”
Section: Importance Of Therapeutic Relationships In Integrated Care O...mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Recent qualitative and mixed-methods studies of individuals with multimorbidity and complexity also reported that these patients expect nurses to be more cognizant of their living situations and social care needs and develop therapeutic interpersonal relationships to enhance the delivery of integrated and compassionate care. 2,15,16 Families of individuals with multimorbidity and complexity and health care teams are important partners in the delivery of person-centered integrated care. 17,18 Scoping reviews have highlighted that enhanced collaboration among health care professionals and families of patients is crucial for the delivery of integrated care.…”
Section: Importance Of Therapeutic Relationships In Integrated Care O...mentioning
confidence: 99%
“…Individuals with multimorbidity and complexity (i.e., complex patients) have multifaceted and emerging complex care needs requiring integrated patient care. 1 - 3 These individuals often live with multimorbidity (ie, two or more chronic conditions) and/or mental health issues, limited education, low socioeconomic status, and/or polypharmacy. 4 Integrated patient care is defined as “patient care that is coordinated across professionals, facilities, and support systems; continuous over time and between visits; tailored to the patients’ needs and preferences; and based on shared responsibility between patient and caregivers for optimizing health.” 5 (p113) Person-centeredness is the core dimension of integrated care, 6 and nurses, patients and their families, and health care teams are the key partners in integrated patient care, among others.…”
mentioning
confidence: 99%
“…Community nurses report increased complexity among older people, requiring additional time and resources to deliver appropriate care (McGeorge, 2011;Whitehead et al, 2021Whitehead et al, , 2023.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Clinical need relates to the types of chronic conditions, how they interact and how they are managed from a medical perspective, the person's understanding of the conditions and how they impact how they live (Whitehead et al, 2023). Thinking about the disease alone or excluding disease when determining the level of complexity could result in a shifted focus, the ICF excluding dementia is an example of this (Spoorenberg et al, 2015).…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation